CHARACTERISTICS AND ORIGIN OF NATURAL GASES IN THE KUQA DEPRESSION OF TARIM BASIN, NW CHINA - Zou Y.-R.; Wang Y.; Peng P.; Shuai Y.; Zhao C.; Zhao W. (My University, 2006)
Significant gas condensate as well as some black oils have been discovered in the Kuqa Depression of Tarim Basin, NW China. Dry gases with high δ13C values occur in the Kelasu structural belt, wet, isotopically light gases in the Yiqikelik belt, whereas condensates are distributed mainly in the Front Uplift area. Kinetic modeling results show that the variation of methane and ethane isotopes with increasing vitrinite reflectance is independent of heating rates for a given source rock. Two maturity trends have been observed on a C2/C1- δ13C1 plot, one for thermogenic gases associated with coal, another for oil-associated gases with minor contribution from biogenic gas. It is most likely that the gases in the Kelasu belt and Front Uplift area were derived from the Jurassic coal measures and Triassic lacustrine shales, respectively, with those in the Yiqikelik belt being the mixtures of gases from the two sources. Both Jurassic coals and Triassic lacustrine shales appear to have contributed to the gases in the Kela 2 (KL2) and Dina 2 (DN2), the two largest gas fields in the Tarim Basin. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Jurassic; Triassic; Mesozoic::Jurassic; Мезозой::Юрская; Mesozoic::Triassic; Мезозой::Триасовая